Adaptation and validation of indicators concerning the sterilization process of supplies in Primary Health Care services - Isis Pienta Batista Dias Passos; Maria Clara Padoveze; Camila Eugênia Roseira; Rosely Moralez de Figueiredo (Universidade de São Paulo, 2015)
OBJECTIVES: to adapt and validate, by expert consensus, a set of indicators used to assess the sterilization process of dental, medical and hospital supplies to be used in PHC services.METHOD: qualitative methodological study performed in two stages. The first stage included a focal group composed of experts to adapt the indicators to be used in PHC. In the second stage, the indicators were validated using a 4-point Likert scale, which was completed by judges. A Content Validity Index of ≥ 0.75 was considered to show approval of the indicators.RESULTS: the adaptations implemented by the focal group mainly referred to the physical structure, inclusion of dental care professionals, inclusion of chemical disinfection, and replacement of the hot air and moist heat sterilization methods. The validation stage resulted in an index of 0.96, which ranged from 0.90 to 1.00, for the components of the indicators.CONCLUSION: the judges considered the indicators after adaptation to be validated. Even though there may be differences among items processed around the world, there certainly are common characteristics, especially in countries with economic and cultural environments similar to Brazil. The inclusion of these indicators to assess the safety of healthcare supplies used in PHC services should be considered.